2017
DOI: 10.1097/scs.0000000000003875
|View full text |Cite
|
Sign up to set email alerts
|

Does a Premaxillary Setback and Lip Adhesion Have a Negative Impact on Lip Outcome in Bilateral Cleft Patients?

Abstract: Bilateral cleft patients with a protruded and deviated premaxilla over 10 mm discrepancy of the lateral maxillary achieved noninferior lip symmetry 1 year postoperatively compared with patients with less severe original deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Severe bilateral cleft lip and palate has been defined as a bilateral cleft lip with alveolar gap wider than 1 cm (in 1 or 2 sides). 13 …”
Section: Methodsmentioning
confidence: 99%
“…Severe bilateral cleft lip and palate has been defined as a bilateral cleft lip with alveolar gap wider than 1 cm (in 1 or 2 sides). 13 …”
Section: Methodsmentioning
confidence: 99%
“…These reports discussed that lip adhesion creates unnecessary scarring from an additional procedure and causes abnormal tethering in the lip and nose elements 15,18,19,21,35 . However, a number of reports state that scarring from lip adhesion does not interfere with the appearance of the lip following lip repair, 10,36 and we also report that during the procedure, with meticulous dissection and without involving essential anatomical landmark, the scarring would not interfere with lip repair. Furthermore, by performing lip adhesion, not only the cleft width is reduced, but also the severe malposition of the maxillary segments can be corrected, thereby allowing inexperienced practitioners to perform lip repair more easily.…”
Section: Discussionmentioning
confidence: 58%
“…The projection of the premaxilla was measured from the alveolar arch of the lateral segment to the premaxillary arch on CT images. It has been reported that patients with bilateral cleft lip with a protruding premaxilla of more than 10 mm achieved noninferior lip symmetry after premaxillary setback with vomerine ostectomy as patients with less severe original deformities 12) .…”
Section: Discussionmentioning
confidence: 99%